Development of a Nondestructive Method for Sexing Live Adult Sternoplax souvorowiana (Coleoptera: Tenebrionidae). Issue 1 (1st May 2015) - Wang, Yan; Ma, Ji; Mao, Xinfang
Abstract : The darkling beetle, Sternoplax souvorowiana (Reitter) (Coleoptera: Tenebrionidae), is flightless and lives in the Guerbantonggut desert in northwestern China. Its special eggshell structure, day-active habit, large body size, short life cycle, and ease of rearing under laboratory conditions make it an excellent model for advanced studies on desert adaptation. Determining the sex of this beetle is usually complicated by the lack of a discreet, externally visible gender-specific character. To date, dissection has been used for sex identification in this species, whereas a nondestructive means is needed for further studies of sexual dimorphism. Here, a new method based on the difference of the pigmentation pattern on the eighth tergite of each sex is described and illustrated. This method can be quickly learned, is nondestructive, is 100% accurate, and is fast enough for most applications in both the field and the laboratory. Experienced users in our laboratory routinely sex 8–10 beetles per minute.